Developing Colorimetric and Luminescence-Based High-Throughput Screening Platforms for Monitoring the GTPase Activity of Ferrous Iron Transport Protein B (FeoB). (June 2019) - Veloria, John; Shin, Minhye; Devkota, Ashwini K.; Payne, Shelley M.; Cho, Eun Jeong; Dalby, Kevin N.
Iron is an essential requirement for the survival and virulence for bacteria. The bacterial ferrous iron transporter protein B (FeoB) functions as a major iron transporter in prokaryotes and has an N-terminal domain (NFeoB) with homology to eukaryotic G-proteins. Its GTPase activity is required for ferrous iron uptake, making it a potential target for antivirulence therapies. Here, two assay strategies relying on different spectroscopic readouts are described to monitor NFeoB GTPase activity. The first one is the colorimetric-based platform that utilizes a malachite green reagent to monitor phosphate production from GTP hydrolysis. The absorbance change directly relates to the GTPase activity of NFeoB. The assay was further improved by the addition of Tween-20 and miniaturized in a 384-well plate format with a 10 µL assay volume. The second format is a luminescence-based platform, measuring the GTP depletion by using a modified GTPase-Glo assay from Promega. In this platform, the luminescence signal correlates to the amount of GTP remaining, allowing for the direct calculation of GTP hydrolysis by NFeoB. The colorimetric platform was tested in a high-throughput manner against a custom-assembled library of a~2000 small molecules and was found to be simple, cost-effective, and robust. Additionally, the luminescence-based platform demonstrated its capability as an orthogonal assay to monitor GTPase activity, providing a valid and convenient method to filter false hits. These two assay platforms are proven to offset the limitations of each platform while enhancing overall quality and success rates.